Surveillance of lymphatic filariasis in selected districts of Nepal - Adhikari, RK; Bhusal, KP (Journal of Institute of Medicine Nepal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Lymphatic Filariasis has been identified by the World Health Organization as a public health problem worldwide including Nepal and targeted for elimination. The present study aimed to determine the prevalence of Lymphatic filariasis in Palpa, Tanahun, Syangja, Gorkha, Sindhupalchok, Rupendehi and Nawalparasi districts as identified by Fiariasis Elimination Programme, World Health Organization/Epidemiological Disease Control Division, Teku, Kathmandu for launching Diethyl carbamazine administration campaign and to develop the better strategies for the delivery of intervention measures in filariasis endemic areas of Nepal. Materials and Methods: A Sentinel surveillance study was carried out among 7,000 (Male-3319, Female-3681) cases and tested for microfilaraemia. The total number of Microfilaraemia positive cases was 55, and the number were 20, 5,10,4,5,7 and 4 in Sindhupalchok, Nawalparasi, Rependehi, Palpa, Tanahu, Syangja and Gorkha districts respectively. The total number of cases having symptoms and signs is 176 and the number were 138,0,28,4,1,5 and 0 in Sindhupalchok, Nawalparasi, Rependehi, Palpa, Tanahu, Syangja and Gorkha districts respectively. Result: The highest microfilariae infection rate was 2.0% in Sindhupalchowk district which is significant in number as compared to other districts and lowest 0.40% in Palpa and Gorkha districts. The highest number of symptomatic cases was found in Sindhupalchowk district 138 (13.8%). One significant finding was that 55 persons were found to be microfilaraemia positive but only 41 persons had symptoms of Lymphatic Filariasis and 14 microfilaraemia positive cases did not have symptoms and signs of filariasis. Conclusion: From these findings it is recommended that diethyl carbamazing administration campaign should be launched in Sindhupalchok, Nawalparasi, Rependehi, Palpa, Tanahu, Syangja and Gorkha districts. Key words: Filariasis, diethyl carbamazine, endemic Journal of Institute of Medicine, April, 2008; 30:1 35-40 The full text of this paper is available from the Journal of Institute of Medicine website